2012
DOI: 10.1002/pca.2379
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activities of Polyphenolic Compounds Isolated from Medicago sativa and Medicago truncatula Assessed by Means of Thin‐layer Chromatography DPPH˙ Rapid Test

Abstract: A simple, rapid and reliable TLC-DPPH˙ test with image processing has been developed enabling comparison of free radical scavenging activity of plant polyphenols. The influence of different structural features on the observed activity was measured successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 16 publications
2
21
0
2
Order By: Relevance
“…In our earlier study we found that NOE exhibited a noticeable anti-inflammatory activity in several animal models of inflammation (17). Moreover, free radical scavenging properties of phenolic and flavonoid compounds were confirmed in some studies (37)(38)(39). In this study, phenolic and flavonoid contents of NOE detected to be 71 ± 6.23 gallic acid equivalents/g dried extract and 95.26 ± 7.6 mg rutin equivalents/g dried extract, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…In our earlier study we found that NOE exhibited a noticeable anti-inflammatory activity in several animal models of inflammation (17). Moreover, free radical scavenging properties of phenolic and flavonoid compounds were confirmed in some studies (37)(38)(39). In this study, phenolic and flavonoid contents of NOE detected to be 71 ± 6.23 gallic acid equivalents/g dried extract and 95.26 ± 7.6 mg rutin equivalents/g dried extract, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…The SAR antioxidant studies of flavonoids have been a subject of number of research proposals [36]. Free hydroxyl groups at C-3 and C-4 positions, C2 C3 double bond, C-3 and C-4 dihydroxy groups are the necessary structural requirements for better antioxidant activity of the flavonoid [36]. Moreover, in case of prenylated flavonoids, the position of prenyl groups on the flavonoid skeleton plays a significant role in imparting antioxidant activity [37].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Flavonoids which produce relatively stable resulting antioxidant radicals can quickly terminate radical chain reaction, and may be considered as effective antioxidants. The SAR antioxidant studies of flavonoids have been a subject of number of research proposals [36]. Free hydroxyl groups at C-3 and C-4 positions, C2 C3 double bond, C-3 and C-4 dihydroxy groups are the necessary structural requirements for better antioxidant activity of the flavonoid [36].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of lentil flavonoids to scavenge DPPH radicals was determined using a TLC rapid test [35]. Briefly, standard solutions (1 mg·mL ) of the purified flavonoids and rutin (positive control) were prepared.…”
Section: Tlc-dpph Testmentioning
confidence: 99%